Collections conservation practices and possibilities of contamination by hazardous pesticides : towards a non-pesticide approach of conserving organic collections at the Natural History Museum of Zimbabwe - O'Connell, Siona (University of Pretoria, 2023)
Thesis (PhD (Heritage and Museum Studies))--University of Pretoria, 2022.